PENINGKATAN PERAN PEMERINTAH DALAM MELINDUNGI HAM KAUM DIFABEL - Phireri Phireri; Muhammad Akbar Fhad Syahril; Muhammad Mufti M. Djafar (Khairun Law Journal, 2024)
Decent work and livelihoods for humanity are part of human rights for everyone, including people with disabilities, so the 1945 Constitution provides guarantees and legal protection for their implementation. The problem is the discriminatory attitude towards persons with disabilities and the low level of education of persons with disabilities as a gap between people with disabilities and non-disabled workers. The absence of exact data related to the number of workers with disabilities both in the private sector and non-private sectors (PNS, BUMN and BUMD) raises its own problems in the protection of persons with disabilities. The quota of minimum requirement is 2 percent as a mandatory for the government, local government, BUMN, and BUMD and 1 percent for private companies from the number of employees or workers in the Disability Act is apparently not enough to provide protection for people with disabilities. This research is a normative legal research to examine the laws and regulations in order to obtain justice for persons with disabilities. This becomes very important as a form of government commitment through supervision and improvement of policies becomes very important so that persons with disabilities get decent work and livelihoods.